Implementation of Angelic Responsibility Traits in Teachers' Duties in the Modern Era: An Islamic Education Perspective - Alza Nabiel Zamzami; Elly Zakiatin Nafisa; Masrur Masrur; Shodiq Abdullah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Implementation of Angelic Responsibility Traits in Teachers' Duties in the Modern Era: An Islamic Education PerspectiveObjective: This study examines the implementation of angelic responsibility for teachers' duties in the modern era from an Islamic educational perspective. Method: This study uses a qualitative approach with hermeneutic analysis based on the Part and Whole theory to understand the role of teachers in teaching knowledge and educating students' character through Islamic teachings, with religious texts as the primary data source. Results: The study shows that the angelic sense of responsibility can enhance the quality of teaching and students' morality and foster an integrity-driven generation. Teachers in the digital age also face challenges in upholding Islamic values amid societal developments. Conclusion: Implementing the angelic trait of responsibility in teacher education in the modern era can serve as a guideline for improving the quality of education and student morality. This trait of responsibility develops academic competencies and students' character according to Islamic teachings. Contribution: This study makes an important contribution to the development of Islamic education curricula, particularly in introducing character values based on Islamic teachings as a foundation for teachers in performing their duties.INDONESIAN: Implementasi Sifat Tanggung Jawab Malaikat Terhadap Tugas Guru di Era Modern: Perspektif Pendidikan IslamObjektif: Penelitian ini bertujuan untuk mengkaji implementasi sifat tanggung jawab malaikat terhadap tugas guru di era modern, dalam perspektif pendidikan Islam. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan analisis hermeneutik berbasis teori Part dan Whole untuk memahami peran guru dalam mengajarkan ilmu dan mendidik karakter siswa sesuai ajaran Islam, dengan teks-teks keagamaan sebagai sumber data utama. Hasil: Penelitian menunjukkan bahwa sifat tanggung jawab malaikat dapat meningkatkan kualitas pengajaran, moralitas siswa, dan membentuk generasi berintegritas. Guru di era digital juga menghadapi tantangan dalam mempertahankan nilai-nilai islami di tengah perkembangan zaman. Kesimpulan: Implementasi sifat tanggung jawab malaikat dalam pendidikan guru di era modern dapat menjadi pedoman dalam meningkatkan kualitas pendidikan dan moralitas siswa. Sifat tanggung jawab ini tidak hanya mengembangkan kompetensi akademik tetapi juga karakter siswa sesuai dengan ajaran Islam. Kontribusi: Penelitian ini memberikan kontribusi penting dalam pengembangan kurikulum pendidikan Islam, terutama dalam memperkenalkan nilai-nilai karakter yang berdasarkan ajaran Islam sebagai dasar bagi guru dalam menjalankan tugasnya.